2003
DOI: 10.1038/sj.gene.6363974
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation-induced gene expression in Ramos B-cells

Abstract: The development of adaptive immunity and responses to foreign molecules and organisms relies on the highly regulated production of hundreds of proteins. B-cell maturation, from committed progenitors to terminally differentiated plasma cells, is a multistep process that requires the ordered expression of a large number of genes. We studied anti-IgM-stimulated Ramos cells to explore genome-wide expression patterns in differentiating human B-cells. cDNA microarrays were used to measure changes in transcript level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 52 publications
(51 reference statements)
5
17
0
Order By: Relevance
“…The envisaged role of PC4 in V(D)J recombination is supported by a microarray analysis of Ramos-B cells stimulated with anti-IgM. 30 It was found that PC4 expression upregulated in 24 h upon stimulation. This may further indicate the role of PC4 in NHEJ, which is part of V(D)J recombination.…”
Section: Discussionmentioning
confidence: 98%
“…The envisaged role of PC4 in V(D)J recombination is supported by a microarray analysis of Ramos-B cells stimulated with anti-IgM. 30 It was found that PC4 expression upregulated in 24 h upon stimulation. This may further indicate the role of PC4 in NHEJ, which is part of V(D)J recombination.…”
Section: Discussionmentioning
confidence: 98%
“…Our GExCo (Gene Expression Correlation) analysis method is based on Spearman linear correlation to monitor covariations between a number of gene parameters and gene expression levels along a time series. Similarly to the protein characteristics study (Sharabiani et al, 2005), clear correlations were evident for all the studied experiments, which contain high-quality datasets for human T cell stimulation (Diehn et al, 2002) and B cell stimulation (Ollila and Vihinen, 2002;Ollila and Vihinen, 2003), innate immune response to infection by L. monocytogenes (Baldwin et al, 2003), human (Whitfield et al, 2002) and yeast cell cycle data (Spellman et al, 1998), and D. melanogaster life cycle data (Arbeitman et al, 2002).…”
Section: Resultsmentioning
confidence: 79%
“…In total, 4359 cDNA elements (of approximately 18,000 genes and ESTs on the chip) representing 2240 genes were significantly altered after CD3 stimulation or CD3/CD28 costimulation (Diehn et al, 2002). The B cell dataset for genes involved in maturation in anti-immunoglobulin M-stimulated Ramos cells indicated that 1268 genes had significantly altered expression, at least at one time point (Ollila and Vihinen, 2002;Ollila and Vihinen, 2003).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…We observed very significant and dynamic correlations in all the datasets we investigated. We investigated several high-quality datasets for different cell types, treatments, and organisms, including human T cell stimulation [20] and B cell stimulation datasets [8,21], yeast cell cycle data [22], and Drosophila melanogaster life cycle data [23]. …”
Section: Resultsmentioning
confidence: 99%